ADVERSE DRUG REACTIONS: CLINICAL ASSESSMENT OF DRUG INDUCED DISEASE - Shah, Shaheen; Shah, Huma; Khaskheli, Meharun Nissa; Akhtar, Junaid (Journal of Ayub Medical College Abbottabad, 2005)
Physicians are often confronted with patients who state that they are allergic to a drug. The goal of this review article is to help physicians to develop management plans for patients who present with drug induced diseases. It provides information that allows physicians to differentiate between reactions that are truly allergic in nature and those that are not immunologically mediated. The suggestions which may be helpful in the assessment are discussed and guidance is provided whether a drug may be safely readministered. Unfortunately until we are unable to thoroughly understand the mechanisms responsible for drug induced reactions, our management tools will remain limited.